CTIM-18. PHASE 2 STUDY OF PD-1 BLOCKADE WITH PEMBROLIZUMAB PLUS RE-IRRADIATION FOR RECURRENT GLIOBLASTOMA (RGBM) (NCT03661723). (14th November 2022) - Iwamoto, Fabio; Tanguturi, Shyam; Desai, Arati; Nayak, Lakshmi; Uhlmann, Erik; Wang, Tony; Lustig, Robert; Hertan, Lauren; Bagley, Stephen; Hayden, Julia; Laforest-Roys, Corey; Muzikansky, Alona; et al.
Abstract: Re-irradiation is therapeutically considered for select rGBM patients and may induce immunogenic cell death to stimulate anti-tumor immune responses. Our phase 2 study of re-irradiation with pembrolizumab among rGBM patients evaluated the efficacy and safety of this regimen. METHODS: Adult rGBM patients with KPS ≥ 70, a maximum supratentorial tumor diameter of 6 cm who were on ≤ 2mg dexamethasone/day and were ≥ 6 months from initial conventional radiation therapy were eligible. Cohort A (bevacizumab [BEV]-naïve) had ≤ 2 prior progressions while cohort B (BEV-refractory) allowed unlimited progressions but only one on prior BEV. Re-irradiation included 35 Gy over 10 fractions to residual enhancing (cohort A) as well as enhancing + non-enhancing (cohort B) disease. Pembrolizumab was administered at 200 mg every three weeks beginning within one week of re-irradiation start. BEV was administered at 15 mg/kg every three weeks for cohort B only. RESULTS: Sixty patients enrolled (n = 30 per cohort) with a median age of 61 years (range 20-76), 47% were female and 53% enrolled after 2 or more progressions. Grade 3 events deemed at least possibly related to study therapy in > one patient for cohort A included headache (n = 2) and for cohort B included elevated ALT (n = 2) and hypertension (n = 5). No grade 4 events occurred in more than single patients per cohort and no grade 5 events occurred. Median PFS and PFS-6 were 4.9 months (95% CI: 3.5, 5.6) and 26.0% (95% CI: 12.3%, 43.0%) for cohort A and 4.14 months (95% CI: 3.45, 5.42) and 16.9% (95% CI: 5.4, 33.7) for cohort B. Median survival for cohorts A and B were 11.5 months (95% CI: 9.6, 14.1) and 7.6 months (95% CI 5.5, 9.3), respectively. CONCLUSIONS: Re-irradiation with pembrolizumab was overall well tolerated and achieved comparable efficacy to historical salvage therapy established with lomustine.